Maturation of Complex Synaptic Connections of Layer 5 Cortical Axons in the Posterior Thalamic Nucleus Requires SNAP25. (26th December 2020) - Hayashi, Shuichi; Hoerder-Suabedissen, Anna; Kiyokage, Emi; Maclachlan, Catherine; Toida, Kazunori; Knott, Graham; Molnár, Zoltán
Abstract: Synapses are able to form in the absence of neuronal activity, but how is their subsequent maturation affected in the absence of regulated vesicular release? We explored this question using 3D electron microscopy and immunoelectron microscopy analyses in the large, complex synapses formed between cortical sensory efferent axons and dendrites in the posterior thalamic nucleus. Using a Synaptosome-associated protein 25 conditional knockout ( Snap25 cKO), we found that during the first 2 postnatal weeks the axonal boutons emerge and increase in the size similar to the control animals. However, by P18, when an adult-like architecture should normally be established, axons were significantly smaller with 3D reconstructions, showing that each Snap25 cKO bouton only forms a single synapse with the connecting dendritic shaft. No excrescences from the dendrites were formed, and none of the normally large glomerular axon endings were seen. These results show that activity mediated through regulated vesicular release from the presynaptic terminal is not necessary for the formation of synapses, but it is required for the maturation of the specialized synaptic structures between layer 5 corticothalamic projections in the posterior thalamic nucleus.